I am I. M. Pei - Meltzer, Brad; Eliopoulos, Christopher (New York : Dial Books for Young Readers, 2021)
"This picture book biography follows I.M. Pei's start as an architect and his lasting impact on buildings all around the world"--Provided by publisher.
"Pop-up inside!"-- Cover.
Keywords: Pei, I. M., -- 1917-2019 -- Juvenile literature; Chinese American architects -- Biography -- Juvenile literature